Pilot implementation study of a web-based men's health screening app in primary care during COVID-19: a mixed-methods approach - Chor Yau Ooi; Chirk Jenn Ng; Anne Sales; Chin Hai Teo (BMC, 2024)
Abstract Background The traditional delivery of healthcare services, including crucial preventive measures such as health screenings, faced significant disruption due to the COVID-19 pandemic. In response, eHealth technology emerged as a practical alternative for conducting screening services. This pilot study introduces ScreenMen, a web-based app for men's health screening, implemented in a primary care setting. The study aims to assess patient uptake and healthcare provider's acceptability and feasibility of implementing ScreenMen, emphasizing the importance of implementation science research in healthcare innovation. Methods This study employed a mixed-method explanatory sequential design, using a tailored implementation intervention to implement ScreenMen in an urban health clinic. Quantitative phase focused on patient uptake of ScreenMen and healthcare provider involvement, utilizing Google Analytics and provider questionnaires. Qualitative phase, using in-depth interviews with providers, explored factors influencing uptake and implementation. Data analysis employed means and percentages for quantitative data and framework analysis for qualitative data. Results We invited 47 healthcare providers to attend the ScreenMen implementation workshop, with 26 participating, resulting in a 55.3% participation rate. Throughout the five-month study, there were 75 recorded accesses, with a completion rate of 20%. The primary way users accessed the app was through QR codes on buntings (38.7%), followed by postcards (12%). In qualitative interviews with three healthcare providers, it was found that the Identify and prepare champions strategy was helpful, as these champions led the implementation and encouraged other providers to promote ScreenMen. The use of QR codes on buntings, part of the Provide education and training strategy, was effective due to their visibility in patient waiting areas. However, the Mandate change strategy was considered ineffective, as providers felt obligated rather than motivated to implement ScreenMen. Conclusion This study highlighted the uptake of ScreenMen and found barriers and facilitators during the pilot implementation. Two useful strategies were Identify and prepare champions and QR codes while Mandate change was not helpful. Further studies are needed to study the effectiveness of these implementation strategies to implement web-based apps. Trial registration Clinical Trial Number: NCT06388473 (Retrospectively registered 05/04/2024).